Penerapan Metode Pakem terhadap Prestasi Belajar Qur’an Hadits Kelas VI MI NW Karang Baru Kecamatan Wanasaba Kabupaten Lombok Timur Tahun Pelajaran 2015/2016 - Asbullah Muslim (PALAPA, 2016)
Singer development research aims to develop the application review methods Pakem Class VI MI NW Karang Baru Academic Year 2015/2016. Research Singer is a Research and Development. Singer Research Development Model development using the Borg and Gall What do WITH the five stages, ie requirement analysis, planning, DRAFT Product Development, Field trials, product revision. Data collection methods used hearts Development Research Singer Was questionnaire responses Students and Students learn the test results.